Factores bio-psico-sociales que influyen en la lactancia materna ineficaz en menores de 6 seis meses de edad en las madres que acuden al Centro De Salud Los Trigales de la ciudad de Guaranda periodo mayo-septiembre 2019 - Allan Agualongo, María José (2019)
his thesis deals with the psychological and social biological factors associated with the abandonment of ineffective breastfeeding in the Los Trigales health center. It aims to establish the factors associated with the abandonment of breastfeeding in mothers of children aged 0 to 6 months. old. Quantitative and qualitative studies of cross-sectional analytical level were carried out, in which 20 mothers from 14 to 35 years old participated in children under 6 months of age, who went to the Los Trigales health center to which a questionnaire of Research related questions. To carry out the research variables through frequency and percentage tables, the estimated results were the following that of 100% of the mothers surveyed, the main causes for the abandonment of breastfeeding fall primarily on the social factor. The biological factor with 50% nipple without preparation, the conclusions being: it was found that the biological and social factors are the factors that influence the abandonment of exclusive breastfeeding there are reasons why breast milk is not continued in the first 6 months of life, the social factor highlighting the work of the mother who copes with a very high percentage 45% in the abandonment of breastfeeding are the most notable factors in the abandonment of breastfeeding. In conclusion we have the ignorance of the mothers about the importance of the nutrients contained in breast milk, the poor breastfeeding technique, the poor position to breastfeed, not stimulate the mammary gland and especially the work of the mother contributed to a ineffective breastfeeding for children under 6 months.